Physicochemical and structural characterization of biochar derived from the pyrolysis of biosolids, cattle manure and spent coffee grounds. Issue 5 (October 2020) - Stylianou, Marinos; Christou, Anastasis; Dalias, Panagiotis; Polycarpou, Polycarpos; Michael, Costas; Agapiou, Agapios; Papanastasiou, Panos; Fatta-Kassinos, Despo
Abstract: In the framework of circular economy, the need of new feedstock materials for the production of alternative new products is of high priority. Biowastes such as manure, sewage sludge (biosolids, BS) and food-waste are used as raw materials for the production of biochar. The present study aims at characterizing biochars produced from three distinct biowastes (i) manure from cattle waste (manure-derived biochar; MDB), (ii) biosolids (BS) from a conventional Urban Wastewater Treatment Plant (UWTP) (biosolids-derived biochar; BDB), and (iii) spent coffee grounds (SCG)-derived biochar (SCGDB). Samples were slowly pyrolyzed in a small-scale kiln with a capacity of 20–24 kg. The samples were heated under nitrogen atmosphere at approximately 6–7 °C min −1 up to the desired temperature (550 °C) and held for 1.5h. The physicochemical characterization of biochars showed the production of alkaline materials with similarities and variations in their characteristics, which depend to the type of feedstock used. The surface area of the raw materials was considerably low (<0.1 m 2 /g) and increased after pyrolysis to 14.03 m 2 /g, 3.98 m 2 /g and 1.53 m 2 /g for MDB, BDB and SCGDB, respectively. The high %C content, the low H/C ratio and the FTIR adsorption peaks revealed high aromaticity, polymerization and carbonization of the biochars and the presence of several functional groups. These, are some of the biochar properties which could lead to different sorption mechanisms of organic and inorganic contaminants. Also, they presented good stability in soil, which enables to be used as soil amendment and C sequestration mechanism. Finally, the produced biochars showed promising properties for environmental applications. Graphical abstract: Image 1 Highlights: Biowastes can be used as feedstock materials for the production of biochar. Biochars from biosolids showed promising properties for environmental applications. Biochar properties showed good stability as soil amendment. Properties of the produced biochars are depended to the type of feedstock used.